PESAN DAKWAH PADA KOMUNIKASI TRADISI POJHIAN HODO DI SITUBONDO - Maisaro; Nur Ainiyah (Fakultas Dakwah Universitas Ibrahimy, 2023)
This paper discusses cultural communication in the Pojhian Hodo tradition. The Pojhian Hodo tradition is the tradition of asking for rain of mercy and also asking for safety. By using a hymn, as well as music and dance. The local people carry out this tradition as a form of respect for their ancestors or ancestors, who have cleared the forest in the area to make it into the Pariopo hamlet. The research method used is descriptive qualitative. namely describing the conditions or symptoms and phenomena that occur in the field which is called Field Research. So it was from here that the author conducted research and went straight into the field to see the condition of the people, even though he did not see the Pojhian Hodo tradition firsthand. From the results of the study, the da’wah messages contained in the Pojhian Hodo tradition, namely the discovery of the values of faith, shari’ah and morals. The tradition carried out by the people in Pariopo Hamlet while carrying out this tradition is an Islamic activity and does not come out of Islamic teachings with the characteristics of the Wali Songo teachings. With the Pojhian Hodo tradition, it is also a way for the people in Pariopo hamlet to strengthen their faith and worship. Indeed, there is no god but Allah and the Prophet Muhammad is the Messenger of Allah. In addition, this tradition is used as entertainment for the community. The aim is for this culture to become part of the life of the Pariopo people which they have lived for generations.